Writing Competence of High School Students in Filipino (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
Writing is one of the essential elements in effective communication that a person needs to possess. Yet both teachers and learners are confronted with the non-realization of the latter on the importance of the skill as illustrated in their academic compositions in school. In this regard, this study was conducted to assess the Level of Writing Skills of Grade 9 students at San Fernando City National Vocational High School in the School Year 2019-2020. It utilized the one-group pre-test-post-test research design to test the effectiveness of an intervention activity in developing the writing competence of the respondents. There were 66 respondents whose parents consented to their participation in this study. Before the implementation of the intervention activity to gather the needed data, the researcher sought permission from the authorities. Descriptive and inferential statistics were both used to treat the gathered data. The results of the respondents' pre-test and post-test scores showed that their writing skills were at an average level. Noteworthy was that the post-test showed gains in the scores though descriptively, these scores fall under the average level. However, the test of difference showed a significant difference in the performance of the students in the pre-test and post-test. This means that the intervention material used to enhance the writing skills of the respondents is effective. This led the researcher to recommend the use of the Skill book to enhance students’ skills in writing.
Keywords: skill book, Grade 9 learners, writing skills